HUBUNGAN DERAJAT HIPERTENSI DENGAN KEJADIAN PREEKLAMSIA-EKLAMSIA DI RSUD dr. MURJANI SAMPIT TAHUN 2018 - nurfitriani nurfitriani (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2019)
Background: Preeclampsia is the second leading cause of maternal death in the world. In Indonesia the incidence of preeclampsia is about 3-10% of pregnancies. Based on the result of preliminary studies in Murjani Hospital Sampit in 2018 get 16,9% pregnant women with preeclampsia are caused by hypertension experienced by mother during pregnancy. Objective: To know the Correlation Hypertension to Preeckalmpsia-Eclampsia in dr. Murjani year 2018. Methods: This research used analytical method with cross sectional design. Research location in dr. Murjani in March – June of 2018 with a sample size of 31 people using primary data with the accidental sampling technique. The independent variables of hypertension and the dependent variable of Preeclampsia-eclamsia event. Results: From the 31 respondents there are 19 respondents (61,3%) with hypertension of degree I, and there are 12 respondents (38,7%) with hypertension of degree II. The frequency of preeclampsia was 18 respondents (58,1%), and frequency does not occur preeclampsia was 13 respondents (41,9%). Conclusion: There is a positive and significant relationship which is indicated by the value of ?- value: 0,008 between the Hypertension correlation with the Preeclampsia in Hospital dr. Murjani 2018.